Stochastic Logistic Systems with Jumps - Ruihua Wu; Ke Wang (Journal of Applied Mathematics)
This paper is concerned with a stochastic nonautonomous logistic model with jumps. In the model, the martingale and jump noise are taken into account. This model is new and more feasible and applicable. Sufficient criteria for the existence of global positive solutions are obtained; then asymptotic boundedness in pth moment, stochastically ultimate boundedness, and asymptotic pathwise behavior are to be considered.